2019
DOI: 10.1111/iji.12456
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the programmed cell death 1 (PDCD1) polymorphisms in susceptibility to systemic lupus erythematosus

Abstract: The failure of immunological tolerance to self‐antigens plays a fundamental role in the pathogenesis of systemic lupus erythematosus (SLE). PD‐1 is an inhibitory receptor for regulating the immune system and preventing development of autoimmune disorders. This study aimed to determine the role of four single‐nucleotide polymorphisms (SNPs) within programmed cell death 1 (PDCD1 or PD‐1) gene and haplotypes defined by these SNPs in susceptibility to SLE in the Iranian population. Blood samples were obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…This genetic variation may affect susceptibility to different diseases through altering gene expressions and protein productions which are critical for survival, development, and functions of the cells [28]. Several lines of evidence indicate that PD-1 haplotypes exert various impacts on the development of different health problems in different populations including BCC, systemic lupus erythematosus (SLE), and squamous cell carcinomas in Iranian [28,29,41], breast cancer in Chinese [26,42], Type 1 diabetes mellitus (T1DM) in Japanese [43], rheumatoid arthritis in Hong Kong Chinese populations [44]. Our data showed that haplotypes of PD1.1 and PD1.6 polymorphisms affected susceptibility to BCC in the Iranian populations, probably through changing the expression level of PD-1.…”
Section: Pd-1 and Its Ligands Have Negative Regulatory Effects On Immmentioning
confidence: 99%
See 1 more Smart Citation
“…This genetic variation may affect susceptibility to different diseases through altering gene expressions and protein productions which are critical for survival, development, and functions of the cells [28]. Several lines of evidence indicate that PD-1 haplotypes exert various impacts on the development of different health problems in different populations including BCC, systemic lupus erythematosus (SLE), and squamous cell carcinomas in Iranian [28,29,41], breast cancer in Chinese [26,42], Type 1 diabetes mellitus (T1DM) in Japanese [43], rheumatoid arthritis in Hong Kong Chinese populations [44]. Our data showed that haplotypes of PD1.1 and PD1.6 polymorphisms affected susceptibility to BCC in the Iranian populations, probably through changing the expression level of PD-1.…”
Section: Pd-1 and Its Ligands Have Negative Regulatory Effects On Immmentioning
confidence: 99%
“…Genome wide association studies (GWAS) have indicated that mutations in genes encoding immuno-inhibitor agents are involved in disrupting immune reactions to developing tumors and subsequently participate in the progressions of different tumors [24,25]. Several lines of evidence indicate that PDCD1 SNPs, such as PD1.1, PD1.3, PD1.5, PD1.6, and PD1.9, may be effective in the development of different cancers and autoimmune disorders [26][27][28][29]. PD1.1 SNP may contribute to the progression of colon cancer [30].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that there was significant increased frequency of PD1.5 C/C genotype in SLE patients compared with healthy cases, while the PD1.5 C/T and T/T genotypes frequencies were reduced in SLE patients. There was also significant correlations between GACT and GGCC haplotypes of PDCD1 and SLE susceptibility, while GGCT was protective during SLE progression [90]. Another group has been reported that there was a significant inverse correlation between PD1.1 GG genotype and juvenile-onset SLE (JSLE) susceptibility among a sub population of Iranian cases.…”
Section: Apoptosis and Dna Repairmentioning
confidence: 96%
“…Despite the role of PD-1 as a negative regulator of T cell activation, it is also essential for the maintenance of Treg cells, which controls the autoimmunity. 104,105 It was also revealed that patients with active SLE have lower PD-1 expression, illustrating a critical role for PD-1 in the pathogenesis of SLE. 106 A study identified CD4+ T cells with oxidized mitochondrial DNA (mtDNA) in blood samples of SLE patients.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 98%